Isolation and Comprehensive Analysis of Cochlear Tissue‐Derived Small Extracellular Vesicles - Pei Jiang; Xiangyu Ma; Xinlin Wang; Jingyuan Huang; Yintao Wang; Jingru Ai; Hairong Xiao; Mingchen Dai; Yanqin Lin; Buwei Shao; Xujun Tang; Wei Tong; et al. (Advanced Science)
Abstract Small extracellular vesicles (sEVs) act as a critical mediator in intercellular communication. Compared to sEVs derived from in vitro sources, tissue‐derived sEVs can reflect the in vivo signals released from specific tissues more accurately. Currently, studies on the role of sEVs in the cochlea have relied on studying sEVs from in vitro sources. This study evaluates three cochlear tissue digestion and cochlear tissue‐derived sEV (CDsEV) isolation methods, and first proposes that the optimal approach for isolating CDsEVs using collagenase D and DNase І combined with sucrose density gradient centrifugation. Furthermore, it comprehensively investigates CDsEV contents and cell origins. Small RNA sequencing and proteomics are performed to analyze the miRNAs and proteins of CDsEVs. The miRNAs and proteins of CDsEVs are crucial for maintaining normal auditory function. Among them, FGFR1 in CDsEVs may mediate the survival of cochlear hair cells via sEVs. Finally, the joint analysis of single CDsEV sequencing and single‐cell RNA sequencing data is utilized to trace cellular origins of CDsEVs. The results show that different types of cochlear cells secrete different amounts of CDsEVs, with Kölliker's organ cells and supporting cells secrete the most. The findings are expected to enhance the understanding of CDsEVs in the cochlea.